Identificação de linhagens avançadas de alface quanto à resistência a Meloidogyne javanica - Ferreira, Sindynara (2011)
The objective of the present work was to evaluate the behavior of lettuce lineages as for resistence to nematode from the Meloidogyne javanica root-knots, identifying probable existence of homozigote lineages for the characteristics. Five F4 and six F5 lineages were used as treatments together with the controls 'Grand Rapids' (resistent) and 'Regina 71' (susceptible), apart from the Santa Clara tomato plant cultivar. The sowing was done over expanded polystyrene trays with the substrate infested by M. javanica eggs in the proportion of 30 eggs cm-3 of substrat. At 47 days after infestation, each plant was evaluated individually as for the following characteristics: visual level of root-knots, number of eggs, level and factor of reproduction. Every lineage was compared to the 'Regina 71' and 'Grand Rapids' for each characteristic, through Dunnett (5%) test, obtaining the significance in relation to each control, allowing the classification of each lineage as resistant homozigote, susceptible homozigote or segregated. The results obtained showed that six lineages (AFX 018C 002 23 15, AFX 018C 002 23 22, AFX 018C 005 42 20, AFX 018C 005 44 22, AFX 018C 005 44 28 and AFX 022B 010 31) were considered resistant homozigote for the evaluated characteristics, and maybe being used as new sources of resistance to M. javanica in lettuce breeding program.